Comparative Effects of Aerobic and Resistance Exercise on Glycaemic Control and Pregnancy Outcomes in Women with Gestational Diabetes Mellitus: A Narrative Review - Szymańska-Zdyb, Kinga; Minik, Bartosz; Nowaczek, Patrycja; Miroński, Adam; Mirkowski, Krzysztof; Cieślewicz, Karolina; Braksal, Barbara; Szurek, Zuzanna Wanda; Chyła, Zofia Julia; Częczek , Kacper (Quality in Sport, 2026)
Background: Gestational diabetes mellitus (GDM) is a common metabolic disorder associated with adverse maternal and neonatal outcomes. Physical activity is recommended as a first-line intervention, but the relative effectiveness of aerobic and resistance exercise remains unclear. Aim: To compare the effects of aerobic, resistance, and combined exercise on glycaemic control and pregnancy outcomes in women with GDM. Methods: A narrative review of studies published between 2014 and 2025 was conducted using PubMed and Scopus. Eligible studies included randomized controlled trials, systematic reviews, and observational studies evaluating exercise interventions in women with GDM. Due to methodological heterogeneity, findings were synthesized narratively. Results: Both aerobic and resistance exercise improved glycaemic control by reducing fasting and postprandial glucose levels and enhancing insulin sensitivity. Resistance training may offer additional benefits for postprandial glucose regulation and reduced insulin requirements. Combined exercise interventions showed the most comprehensive metabolic improvements, although direct comparisons were limited by variability in study protocols. Evidence regarding maternal and neonatal outcomes remained inconsistent. Conclusions: Aerobic and resistance exercise are safe and effective strategies for managing GDM, with potential complementary benefits when combined. However, heterogeneity of interventions and limited sample sizes prevent definitive conclusions regarding the superiority of any single exercise modality. Further high-quality randomized controlled trials with standardized protocols are needed to inform evidence-based recommendations.